Transformation and Islamic Inculturation in the Ludruk Performing Art of Surabaya, 1975–2022: A Study of Social and Cultural History - Daul Ibad (Warisan: Journal of History and Cultural Heritage, 2025)
This study investigates the process of Islamic inculturation within the traditional performing art of ludruk in Surabaya from 1975 to 2022, situating the analysis within the theoretical framework of inculturation and social history. It seeks to examine how Islamic values have been internalized into the structural, narrative, and symbolic dimensions of ludruk without diminishing its identity as a popular folk performance. Employing historical research methods—namely heuristics, source criticism, interpretation, and historiography—the study draws upon interviews, field observations, documentation, and library research. The findings indicate that Islamic values have been substantively integrated into ludruk through morally grounded plot constructions emphasizing justice and ethical conduct, the representation of religiously conscious protagonists, dialogical expressions infused with ethical-religious nuance, and visual symbolism—such as costumes and stage design—that reflects Islamic identity. Rather than displacing the traditional character of ludruk, this process has reconstituted its cultural function as both a medium of social expression and a vehicle for contextualized religious outreach. The study argues that the relationship between Islam and ludruk represents a long-term, dynamic process of cultural negotiation within the urban social landscape of Surabaya, extending beyond superficial symbolic acculturation.